SIGNAL: Sar for Ice, Glacier and Global Dynamics - Börner, Thomas; De Zan, Francesco; López-Dekker, Francisco; Krieger, Gerhard; Hajnsek, Irena; Papathanassiou, Kostas; Villano, Michelangelo; Younis, Marwan; Danklmayer, Andreas; Dierking, Wolfgang; Nagler, Thomas; Rott, Helmut; et al. (2010 IEEE International Geoscience and Remote Sensing Symposium, 2010)
SIGNAL is an innovative earth exploration mission proposal with the main objective to estimate accurately and repeatedly topography and topographic changes associated with mass change or other dynamic effects on glaciers, ice caps and polar ice sheets. Elevation measurements are complemented with glacier velocity measurements, providing valuable additional information for a better understanding of the hydrology of glacierized basins and of the Arctic and Antarctic water cycle. SIGNAL is capable of monitoring all critical regions with a high spatial resolution and an adequate revisit time. This paper gives an overview about the actual mission design status and provides a brief description of the topography (DEM – digital elevation map) self-calibration strategy and the estimated global interferometric performance.